Using packaged software for solving two differential equation problems that arise in plasma physics - 436271 Gaffney, P. W.; Conference on Elliptic Problem Solvers (1980 : Santa Fe) (Oak Ridge, Tenn : Oak Ridge National Laboratory, Computer Sciences Division, 1980)
40